Effects of temperature on the cellulose binding ability of cellulase enzymes - Andreaus, Juergen (1999)
The effects of high temperatures on catalytic activity and binding abilities of crude Trichoderma reesei cellulases in solution and adsorbed to a cotton fabric were studied. Above optimum temperature of 50 degrees C, catalytic activities were severely diminished but the binding behaviour was not found to be adversely affected. In order to verify possible applications of cellulases adsorbed to cotton fabrics as anchors for textile finishing purposes, we also checked the binding abilities after ironing. Previous ironing of cellulase adsorbed fabrics increased dyeability with an acid dye, but dye fastness was poor. Desorption of cellulases from cotton fabrics increased from pH 5 to pH 10. Dry ironing of fabrics resulted in less desorption, whereas wet ironing inhibited desorption at pH 5 and only 11% of protein were desorbed at pH 10. Ironing of the fabrics diminished enzyme activity of desorbed cellulases. Wet ironing resulted in complete denaturation of the proteins and no cellulolytic activity was found. The presence of water during thermal treatment of cellulases was found to be essential for complete denaturation and unfolding of the proteins. Dry heat only resulted in partial denaturation. Fluorescence measurements of cellulases adsorbed to cotton fabrics showed after ironing a significant shift in tryptophan fluorescence to higher wavelengths. This indicates unfolding and denaturation of the enzymes and revelation of more hydrophobic amino acids to the surface, which enables increased hydrophobic interactions with the fabric. (C) 1999 Elsevier Science B.V. All rights reserved.